Heterogeneous clienteles and dealer networks - Sambalaibat, Batchimeg (Journal of Financial Economics, 2025)
This paper studies a search-based model of OTC markets in which clients with heterogeneous trading needs direct their trades to one of ex-ante identical dealers. The main insight of the paper is that the way clients sort across dealers shapes dealer-to-dealer trading patterns and, in turn, generates a core–periphery interdealer network structure. Dealers in the model become heterogeneous because they attract different clients in equilibrium. Some dealers attract clients who trade frequently (e.g., index funds); others attract clients with infrequent trading needs (e.g., pension funds). Dealers attracting clients with frequent trading needs receive a larger volume of client orders, trade more with other dealers, and, as a result, form the core of the interdealer network. Conversely, dealers specializing in clients with infrequent trading needs form the periphery. I also show that accounting for client heterogeneity across dealers (a) challenges standard measurements and interpretations of bid–ask spreads and (b) generates predictions on bid–ask spreads and dealer centrality consistent with the empirical literature.